Chemical Composition of Date-Pits and Its Potential for Developing Value-Added Product - a Review - Hossain Mohammad Zakir; Waly Mostafa I.; Singh Vandita; Sequeira Venitia; Rahman Mohammad Shafur (Polish Journal of Food and Nutrition Sciences)
Moisture, protein, oil and carbohydrate contents of date-pits varied from 3.1-12.5, 2.3-6.9, 5.0-12.5 and 70.9-86.9 g/100 g date-pits, respectively. BET-monolayer (i.e. strongly bound) moisture content, solids-melting peak (at moisture: 6.7 g/100 g date-pits), and melting point of oil were 4.3 g/100 g dry-solids, 106oC, and 1.8oC, respectively. The major fatty acids were lauric, myristic, palmitic, stearic, oleic, and linoleic acids and polyphenol content varied from 21.0-62.0 mg/g date-pits depending on the varieties, types of solvent and temperature used for extraction. Date-pits showed effectives in animal and poultry feeds and it could be used as value added products, such as: dietary fibres, functional polysaccharides, caffeine-free drinks (similar to coffee), oil (biofuel or cooking oil), and other functional or medicinal products. Date-pits powder and activated carbon from date–pits showed effective in purifying water by removing different types of pollutants, such as heavy metals, boron, dyes, phenolic compounds, and pesticides. Date-pits also showed effective to be used as ingredient for composed, biomass, and fermentation processes.